2019
DOI: 10.1155/2019/4957878
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Herpesvirus 1 Productive Infection Led to Inactivation of Nrf2 Signaling through Diverse Approaches

Abstract: Bovine herpesvirus type 1 (BoHV-1) is a significant cofactor for bovine respiratory disease complex (BRDC), the most important inflammatory disease in cattle. BoHV-1 infection in cell cultures induces overproduction of pathogenic reactive oxygen species (ROS) and the depletion of nuclear factor erythroid 2 p45-related factor 2 (Nrf2), a master transcriptional factor regulating a panel of antioxidant and cellular defense genes in response to oxidative stress. In this study, we reported that the virus productive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…To confirm that Trolox inhibits the activation of the NRF2 pathway induced by arsenite, we examined the effect of Trolox on arsenite-induced intranuclear NRF2 protein levels. As shown in Figure 6 d, Trolox alone increased the NRF2 protein level, as previously reported [ 38 , 39 ], although it did not change the t-PA mRNA expression ( Figure 5 b). When we calculated the ratio of NRF2/Lamin A in the arsenite-treated groups to that in the corresponding control groups, and we found that the arsenite-induced increase in the NRF2 protein ratio was decreased by 1-mM Trolox treatment ( Figure 6 e).…”
Section: Resultssupporting
confidence: 88%
“…To confirm that Trolox inhibits the activation of the NRF2 pathway induced by arsenite, we examined the effect of Trolox on arsenite-induced intranuclear NRF2 protein levels. As shown in Figure 6 d, Trolox alone increased the NRF2 protein level, as previously reported [ 38 , 39 ], although it did not change the t-PA mRNA expression ( Figure 5 b). When we calculated the ratio of NRF2/Lamin A in the arsenite-treated groups to that in the corresponding control groups, and we found that the arsenite-induced increase in the NRF2 protein ratio was decreased by 1-mM Trolox treatment ( Figure 6 e).…”
Section: Resultssupporting
confidence: 88%
“…It has been reported that Nrf2 degradation caused by viral infection is regulated by Keap1-dependent or Keap1-independent ubiquitin–proteasome pathways [ 19 ]. Bovine herpesvirus type infection stimulates Nrf2 degradation through the Keap1-dependent ubiquitin proteasome pathway [ 20 ]. However, Dengue virus uses the NS2B3 protease complex to strategically target Nrf2 for degradation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like other Herpes viruses, BHV-1 maintains its presence throughout the host’s lifespan and can be passed onto calves . Downstream effects of infection include upregulation of genes involved in responding to reactive oxygen species (ROS) . BHV-1 is also known to cause reproductive tract disease in infected cattle, resulting in infertility, miscarriages, and stillbirths. , Clinical signs of BHV-1 include a high fever, inflamed nares, and excessive nasal discharge …”
Section: Pathogens Involved In Brdmentioning
confidence: 99%